Analisis Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Kinerja Pegawai - Imama Rifai; Eka Sudarusman (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
AbstractOrganizational culture is a system values and beliefs that are shared by people who interact in an rganization that serves as an identity and as reference behavior to achieve organizatinal goals. One of the success factor of an organization goals is leadership, especially leadership style will determine the perfomance of an organization that is shown on the employees performance. This study tried to assess the relationship of organizational culture and leadership style influence on employee performance. The object of this study were employees in Badan Pemberdayaan Masyarakat, Perempuan, dan Keluaraga Berencana in Magelang district. The result in multiple regression analysis showed that organizational culture and the leadership style have significant positive effect on employee performance either partially (t test) and simultaneously (F test)